Predictive analysis of water resource carrying capacity based on system dynamics and improved fuzzy comprehensive evaluation method in Henan Province - Ji, Juntao; Qu, Xiaoning; Zhang, Quan; Tao, Jie (Environmental monitoring and assessment, 2022)
The water resource carrying capacity (WRCC) is a carrying capacity of natural resources. It affects the application and expansion of the carrying capacity of water resources. This subject involves various elements, such as water resources, the ecological environment system, humans and their economic and social systems, and a wider range of biological groups and their survival needs. Based on the objective recognition of the complex relationship between the water resource system, ecological environment system, and economic and social system, the support scale of water resources and the ecological environment for economic and social development is studied. Current research on the carrying capacity of water resources has mostly shifted from the previously limited support capacity of water resources to include factors such as the population, economy, and ecology, establishing the internal relationships between the economics, water resources, and ecological environment. This reflects the comprehensive carrying capacity of the entire region (or river basin) of water resources and the ecological environment system on an overall economic and social scale. Based on the conceptual connotation of the WRCC and the actual problems facing water resources in Henan Province, the paper uses a system dynamics method to develop information feedback between the four subsystems of Henan Province: economic, population, water resource, and water environment subsystems. The index system of the WRCC in Henan Province is also determined. The weight of each index is comprehensively determined by a combination weighting method of the analytic hierarchy process and an entropy weight method, and then a fuzzy comprehensive evaluation method is used to evaluate the WRCC of Henan Province under four different development models. The validation period of the model is 2010–2020, and the forecast period is 2021–2030. The results indicate that during the period 2021–2030, the WRCC of Henan Province showed a slight upward trend overall under the four models, but the increase rates were different under the different models. Among the four models, the comprehensive model’s benefit was the best, which not only maintained the healthy and stable development of the economy and society but also improved the pressure on the water resources and the quality of the water environment.